Hand gesture recognition and voice conversion system for dump people (International Journal of Food and Nutritional Sciences, 2022)
This project is based on converting the audio signals receiver to text using speech to textAPI. Speech to text conversion comprises of small, medium and large vocabularyconversions. Such systems process or accept the voice which then gets converted to theirrespective text. This paper gives a comparative analysis of the technologies used in small,medium, and large vocabulary Speech Recognition System. The comparative studydetermines the benefits and liabilities of all the approaches so far.